The Level of Knowledge Among the Potential Tourist Industry Personnel, i.e. Students of Geography and Tourism and Recreation, in the Context of Deregulation of the Tour Guide and the City Guide Professions - Warcholik, Witold (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
This article analyzes the results of the simulation of the tour guide and city guide state theoreticalexamination carried out among the potential tourist industry personnel in order to assess the levelof their knowledge in the context of the planned deregulation of the above mentioned professions. Themock exam participants were part-time and full-time students of the following departments: the first, second and third year of the B.A studies in Tourism and Recreation and the B.A. studies in Geography,the first and second year of the M.A. studies in Geography, and the post-diploma studies in Geography.What was observed was a high rate of positive results in the tour guide state theoretical mock exam,which suggests a good level of knowledge among the participants when seeking employment subsequentto deregulation. Therefore, the results question the current requirement for these groups of studentsto participate in preparatory courses prior to signing up for the state examination. Additionally, themock exam results have helped to distinguish groups of subjects with the lowest pass rate: for theTourism and Recreation program it is Tourism Geography of Poland, and for the Geography program itis History of Art and Culture. It has been pointed out, that there is a significant disproportion in the levelof difficulty between the city guide and the tour guide state theoretical exams, as well as the percentageof positive results achieved among examinees on individual levels. Students assess the city guide stateexam as very difficult and feel the need to attend relevant additional training prior to taking it.